2015
DOI: 10.4067/s0718-221x2015005000038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moisture content on the wave velocity to estimate the mechanical properties of large cross-section pieces for structural use of Scots pine from Spain

Abstract: The aim of this research is to evaluate the influence of the moisture content of wood on stress wave velocity, as a nondestructive technique for estimating the mechanical properties of gross cross-section Spanish Scots pine (Pinus sylvestris) lumber for structural use. 26 100 x 150 x 3000 mm pieces from Segovia, Spain, were tested with different moisture content values, from 35,5 to 9%. Measurements of longitudinal stress wave velocity were carried out during the natural drying process by using three commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This difference in level of E a between dynamic test methods is in line with the literature, which reports that axial dynamic stiffness in timber is typically overestimated 10-20% by Tof [25,74], and previous test results on 100 control and 100 TM boards tested 'directly' [22]. Levels of mean E a and MC of control and TM boards were inversely related (Figure 8a), and are consistent with established E a -MC relationships for unmodified timber [33,75,76]. Significant differences in mean values of E a,tof and E a,res were found between measurement intervals for control boards (one-way ANOVA, p < 0.001), but not for TM boards (one-way ANOVA, p > 0.05) (Figure 8b).…”
Section: Non-destructive Testssupporting
confidence: 89%
“…This difference in level of E a between dynamic test methods is in line with the literature, which reports that axial dynamic stiffness in timber is typically overestimated 10-20% by Tof [25,74], and previous test results on 100 control and 100 TM boards tested 'directly' [22]. Levels of mean E a and MC of control and TM boards were inversely related (Figure 8a), and are consistent with established E a -MC relationships for unmodified timber [33,75,76]. Significant differences in mean values of E a,tof and E a,res were found between measurement intervals for control boards (one-way ANOVA, p < 0.001), but not for TM boards (one-way ANOVA, p > 0.05) (Figure 8b).…”
Section: Non-destructive Testssupporting
confidence: 89%
“…For wood we can assume that with a decrease in moisture content within 0 -FSP will increase the speed of ultrasonic (Mishiro 1995;Montero et al 2015), what was confirmed for Douglas fir, black locust, maple, poplar and alder. Thus, for these kinds of wood, the ultrasonic cannot clearly detect the initial stages of damage.…”
Section: Discussionmentioning
confidence: 82%
“…Specifically, estimating the MOE from the dynamic MOE (MOE d ) obtained from the measured ultrasonic wave velocity has been studied by many researchers. [27][28][29] However, the viscoelastic nature of wood, which leads to an increase in MOE d with frequency, causes the MOE d to overestimate the static MOE. [29][30][31][32] Thus, the accurate nondestructive estimation of the elastic properties of wood materials has remained challenging.…”
Section: Introductionmentioning
confidence: 99%